Forms of Cooperation Between Religions; A Tafsir Perspective - Sismanto, Sismanto; Riswadi, Riswadi (Program Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
Indonesians have different backgrounds; they can live in harmony and side by side without any friction and conflict due to cooperation between religions in an excellent multicultural frame. The research approach is library research. The primary data source used is the Qur'an with the thematic method, while secondary data is in books, journals, and documentation. The study findings show; (1) the cooperation verses in the Qur'an, fifteen verses have the Madaniyah status, and seven verses have the Makiyah status. These verses are grouped into three things: cooperation based on Islamic brotherhood, cooperation based on ukhuwah wathaniyah or nationality, and cooperation based on ukhuwah basyariah human-based. Somebody can carry out a partnership based on ukhuwah basyariah in a multicultural context can be carried out in the political, economic, cultural, and social fields. (2) The hadiths related to the cooperation verses are found in Sahih Muslim numbers 2704 and 2705, Sahih Bukhari numbers 2124 and 2811, Sunan Nasai numbers 3867 and 3871. Based on the transmission line, the hadith is agreed to be a valid hadith even though there are differences in the text, but the meaning has the same substance.